Sistemas eletrônicos com elevado fator de potência de estágio único e sem capacitores eletrolíticos para acionar LEDs de potência - Fonseca, Zito Palhano da (2014)
Two single-stages high-power-factors converters without DC bus electrolytic capacitors for power LEDs applications are proposed in this work. The power factor correction of the first proposed topology is obtained through direct link of one boost inductor connected between the output inverter stage and two capacitors placed before of input bridge rectifier. In the second proposed lighting system, the power factor correction is performed by two magnetically coupled inductors placed at input bridge rectifier that also operate with the two input capacitors and the output inverter stage. In this case, the coupled inductors magnetic fluxes are complementary and their core is reduced when compared with the inductor of the first proposal. In both converters the input voltage provides instantaneous ripple current with twice switching frequency of the output inverter and the input filter inductor is reduced. To obtain continuous current on the LEDs, one output rectifier placed between output inverter stage and a neutron point (NP) of the two DC bus capacitors is used. The LEDS current is limited by a serie inductor. Through steady-state operation the main theorical waveforms as well as the converters design methodologies are presented. To verify the theoretical analysis carried out, simulation and experimental results are also presented. To verify the theoretical analysis, also simulation and experimental results using 12 LEDs connected in series with a power of 45 W, suplied at 127 V and 220 V are presented to validate the methodology proposed projects.